Estimates of the separation between the geoid and the quasigeoid over Australia - Featherstone, Will; Kirby, Jonathan (Institution of Surveyors, Australia, 1998)
The geoid is the equipotential surface to which orthometric heights are referred, whereas the quasigeoid is the non-equipotential surface to which normal heights are referred. The Australian Height Datum is a hybrid of these vertical datum surfaces, being called a normal orthometric height system. It is therefore appropriate to determine the separation between these reference surfaces with a view to future gravimetric determinations of the geoid or quasigeoid of Australia. Using Bouguer gravity anomalies and a digital elevation model, the maximum separation between these surfaces has been estimated to be ~150 mm, with a standard deviation of 218 mm, in Australia. When compared to 129 Global Positioning System and Australian Height Datum control points across the continent, the inclusion of the quasigeoid-to-geoid separation term makes no difference to the standard deviations of the differences. This indicates that the determination of either the geoid or the quasigeoid is appropriate for the determination of Australian Height Datum heights from the Global Positioning System in Australia.